Addressing sophisticated misconceptions: an assimilation-based method for teaching accounting expenses - Zhou, Yining; Javed, Kanwal; Iveson, John (Frontiers in Education, 2025)
Instructors often operate under the assumption that misconceptions stem from a preliminary, untutored, and pre-disciplinary context, leading them to traditionally adopt a refutational method inspired by the Piagetian principle of accommodation to address these naïve misconceptions. This research critiques the traditional refutational method, highlighting its problems in addressing sophisticated misconceptions embedded within a student’s conceptual ecology. These problems include students’ difficulty in abandoning their pre-existing conceptions, their struggle to initiate cognitive conflicts, and a loss of confidence for further learning due to disparity between prior understanding and new conceptions. This paper proposes an innovative solution rooted in the other Piagetian principle of assimilation, which leverages preconceptions as a foundation for initiating conceptual change. The study implements this innovative solution through a series of analogies organized in an assimilative sequence, where each analogy builds upon the previous one to correct specific misconceptions and establish a foundation for subsequent understanding. This approach enables students to become familiar with the case setting as they progress through the study of previous analogies and misconceptions, thereby enhancing their understanding when encountering subsequent analogies and misconceptions. This methodology is exemplified through an accounting educational case study involving five sequential analogies designed to rectify expense-related misconceptions. The successful classroom application of this assimilation-oriented method indicates its potential as a valuable framework for educational researchers and practitioners.